1994
DOI: 10.1007/bf00156751
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of marginal densities for parameters of multinomial distributions

Abstract: The full Bayesian analysis of multinomial data using informative and flexible prior distributions has, in the past, been restricted by the technical problems involved in performing the numerical integrations required to obtain marginal densities for parameters and other functions thereof. In this paper it is shown that Gibbs sampling is suitable for obtaining accurate approximations to marginal densities for a large and flexible family of posterior distributions-the d family. The method is illustrated with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, MCMC methods have proved e ective for the e cient calculation of posterior quantities of interest in contingency table problems with just a single model under consideration. See Epstein and Fienberg (1991) and Forster and Skene (1994) for details. Green (1995) considered the general model determination problem introduced in Section 1.…”
Section: Markov Chain Monte Carlomentioning
confidence: 99%
See 2 more Smart Citations
“…For example, MCMC methods have proved e ective for the e cient calculation of posterior quantities of interest in contingency table problems with just a single model under consideration. See Epstein and Fienberg (1991) and Forster and Skene (1994) for details. Green (1995) considered the general model determination problem introduced in Section 1.…”
Section: Markov Chain Monte Carlomentioning
confidence: 99%
“…They showed that the univariate conditional distributions required for sampling are log-concave, and hence adaptive rejection sampling (Gilks and Wild, 1992) is straightforward to implement. Forster and Skene (1994) used a Gibbs sampler to generate from posterior distributions arising from multinomial likelihoods and logistic normal prior distributions, which corresponds to the situation in the present example. They showed that the Gibbs sampler is extremely e cient when a particular parameterisation, where the parameters are approximately a posteriori independent, is adopted.…”
Section: Reversible Jump Mcmc For Log-linear Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of this strategy in the context of the air pollution data analysis is discussed in Section 4. Alternative MCMC strategies for generating samples from the Aitchison distribution are discussed by Forster and Skene (1994).…”
Section: Methodsmentioning
confidence: 99%
“…However, Markov chain Monte Carlo (MCMC) simulation techniques can overcome the computational problems, even for posterior densities of high dimensionatity or complexity. See, for example, Forster and Skene (1994) who estimate marginal posterior densities for multidimensional tables arising from an intractable prior family of distributions.…”
Section: Introductionmentioning
confidence: 99%